Retinal thickness correlates with parietal cortical atrophy in early‐onset Alzheimer's disease and controls - Jurre denHaan; Sarah F. Janssen; Jacoba A. van deKreeke; Philip Scheltens; Frank D. Verbraak; Femke H. Bouwman (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2018)
Abstract Introduction The retina may reflect Alzheimer's disease (AD) neuropathological changes and is easily visualized with optical coherence tomography (OCT). Retinal thickness decrease has been correlated to AD, however, without information on amyloid status. We correlated retinal (layer) thickness to AD biomarkers in amyloid‐positive early‐onset AD (EOAD) patients and amyloid‐negative controls. Methods We measured macular thickness and peripapillary retinal nerve fiber layer thickness with OCT in 15 EOAD patients and 15 controls and correlated retinal thickness to visual rating scores for atrophy on magnetic resonance imaging. Results Total macular thickness correlated to parietal cortical atrophy in both groups (Spearman ρ −0.603, P = .001). Macular and peripapillary retinal nerve fiber layer thicknesses were not significantly decreased in EOAD compared to controls. Discussion Retinal thickness does not discriminate EOAD from controls but is correlated to parietal cortical atrophy in both groups. These findings may suggest reflection of cerebral cortical changes in the retina, independent of amyloid.